KINETICS OF NUTRIENT UPTAKE BY ECONOMICAL VEGETABLE SPECIES GROWN IN CONSTRUCTED WETLANDS - Haq Nawaz Abbasi; Jing Xie; Jan Vymazal; Xiwu Lu (Journal of Animal and Plant Sciences, 2018)
Constructed wetlands are used to treat wastewater, however, their performance and usage can be improved by selecting a suitable substrate. Various plants may differ in their capacity to assimilate nutrients in a constructed wetland system. In this research, Michaelis-Menten kinetic (Michaelis-Menten constant (K ) and maximum uptake rate ( I )) provides a m max useful tool for the identification of plant nutrient uptake efficiency and selection of plants. Six economical plant species (Phyllostachysheteroclada, Medicago hispidaGaertn, Ipomoea aquatica, Brassica junceavar, Colocasiaesculenta L. Schoot, and A. tubersomrottle ex spreng) were selected to investigate the uptake kinetics. I. aquatica showed a higher maximum uptake capacity for all three nutrients (PO -P, NO -N and NH -N). The second highest uptake capacity for 4 3 4 PO -P, NO -N and NH -N was found for A. tuberosum, B. juncea and M. hispida. I. aquatica has the highest I and 4 3 4 max lowest K values for all three nutrients and it has good capabilities to adjust in high PO -P, NO -N and NH -N nutrient m 4 3 4 condition. I and K of P.heteroclada were relatively small and suitable for the low nutrients concentration max m environment, whereas the I and K of A. tuberosum, M. hispidaand B. juncea were relatively large, which is suitable max m for treating wastewater with high nutrient concentration. m max Constructed wetland. There is an important need to understand the efficiency of
Keywords: Uptake kinetics; Michaelis-Menten kinetic; Michaelis-Menten constant (K ); Maximum uptake rate (I )